2024
DOI: 10.1038/s41598-024-54769-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gut microbiota between Dutch and South-Asian Surinamese: potential implications for type 2 diabetes mellitus

Eric I. Nayman,
Brooke A. Schwartz,
Michaela Polmann
et al.

Abstract: Gut microbiota, or the collection of diverse microorganisms in a specific ecological niche, are known to significantly impact human health. Decreased gut microbiota production of short-chain fatty acids (SCFAs) has been implicated in type 2 diabetes mellitus (T2DM) disease progression. Most microbiome studies focus on ethnic majorities. This study aims to understand how the microbiome differs between an ethnic majority (the Dutch) and minority (the South-Asian Surinamese (SAS)) group with a lower and higher pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…This phenomenon interferes with the digestion and absorption of fats and carbohydrates and exacerbates disturbances in glucose and lipid metabolism. Adverse alterations in GM derivatives also exacerbate the symptoms of T2DM, such as a decrease in short-chain fatty acids (SCFAs) and bile acids (BAs), and an increase in lipopolysaccharides, exacerbating inflammation and insulin resistance ( 12 , 13 ). As early as 2008, researchers have found that changes in GM can control intestinal permeability and metabolic endotoxemia in high-fat-fed mice, a phenomenon that can have an impact on inflammation in obesity and diabetes ( 14 ) and that pharmacological interventions can also improve glucose tolerance in mice by modulating GM ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon interferes with the digestion and absorption of fats and carbohydrates and exacerbates disturbances in glucose and lipid metabolism. Adverse alterations in GM derivatives also exacerbate the symptoms of T2DM, such as a decrease in short-chain fatty acids (SCFAs) and bile acids (BAs), and an increase in lipopolysaccharides, exacerbating inflammation and insulin resistance ( 12 , 13 ). As early as 2008, researchers have found that changes in GM can control intestinal permeability and metabolic endotoxemia in high-fat-fed mice, a phenomenon that can have an impact on inflammation in obesity and diabetes ( 14 ) and that pharmacological interventions can also improve glucose tolerance in mice by modulating GM ( 15 ).…”
Section: Introductionmentioning
confidence: 99%